Analysis and Verification of Traction Motor Iron Loss for Hybrid Electric Vehicles Based on Current Source Analysis Considering Inverter Switching Carrier Frequency - Jin-Hwan Lee (MDPI AG, 2021)
In this study, a current source analysis method considering the inverter switching frequency is proposed to improve the precision of loss analysis of a traction motor for a hybrid electric vehicle. Because the iron loss of the traction motor is sensitively influenced by input current fluctuations, the current source analysis using the actual current obtained from an inverter is the ideal method for accurate analysis. However, as the traction motor and inverter should be manufactured to obtain the real current, the traction motor is generally designed based on an ideal current source analysis. Our proposed method is an analytic technique that fits the loss of a traction motor similar to the actual loss by injecting harmonics of the same order of the inverter switching frequency into the ideal input current. Our method is compared with the analysis of the ideal current source to assess the difference in loss. In addition, a test motor was manufactured, and an efficiency test was conducted to compare the efficiency and verify the effectiveness of our method.